Cofactor engineering for improved production of 2,4-dihydroxybutyric acid via the synthetic homoserine pathway - Ihle, Nadine; Grüßner, Laura; Alkim, Ceren; Nguyen, T. A. Stefanie; Walther, Thomas; Frazão, Cláudio J. R. (Frontiers in Bioengineering and Biotechnology, 2025)
(L)-2,4-dihydroxybutyrate (DHB) is a versatile compound that can serve as a precursor for the synthesis of the methionine analog 2-hydroxy-4-(methylthio)butyrate and new advanced polymers. We previously implemented in Escherichia coli an artificial biosynthetic pathway for the aerobic production of DHB from glucose, which relies on the deamination of (L)-homoserine followed by the reduction of 2-oxo-4-hydroxybutyrate (OHB) and yields DHB by an enzyme-bearing NADH-dependent OHB reductase activity. Under aerobic conditions, using NADPH as a cofactor is more favorable for reduction processes. We report the construction of an NADPH-dependent OHB reductase and increased intracellular NADPH supply by metabolic engineering to improve DHB production. Key cofactor discriminating positions were identified in the previously engineered NADH-dependent OHB reductase (E. coli malate dehydrogenase I12V:R81A:M85Q:D86S:G179D) and tested by mutational scanning. The two point mutations D34G:I35R were found to increase the specificity for NADPH by more than three orders of magnitude. Using the new OHB reductase enzyme, replacing the homoserine transaminase with the improved variant Ec.AlaC A142P:Y275D and increasing the NADPH supply by overexpressing the pntAB gene encoding the membrane-bound transhydrogenase yielded a strain that produced DHB from glucose at a yield of 0.25 molDHB molGlucose−1 in shake-flask experiments, which corresponds to a 50% increase compared to previous producer strains. Upon 24 h of batch cultivation of the most advanced DHB producer strain constructed in this work, a volumetric productivity of 0.83 mmolDHB L−1 h−1 was reached.